PENGARUH STRATEGI PEMBELAJARAN TEAM TEACHING DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR MENGANALISIS RANGKAIAN LISTRIK - Furi Endang Palupi; Soeprijanto; Farried Wadjdi (Journal of Electrical Vocational Education and Technology, 2017)
This study aims to determine the effect of learning team teaching strategy and student learning motivation on the results of learning to analyze electrical circuits. This research was conducted at SMKN 1 Tambelang in February 2017. The sample of this research is students consisting of 2 classes of experimental class of students taught with team teaching amounted to 30 students and control class of students who were taught non-team teaching consisted of 30 Students so the total amounted to 66 students. Of the 66 students were given a questionnaire about student learning motivation, the results will be grouped into 2 ie students who have high motivation and students who have low motivation. Normality data test using lilefors test obtained by each group data and normal distributed line. The result of homogeneity using bartlett test which result of the data is homogeneous. Hypothesis test with F test of Anava 2X2 with significant level 0,05. From the test results obtained F count values between treatments = 49.824 and F table = 4,196. It can be concluded that F count > F table, it can be concluded that overall there is a real difference between team teaching and non-team teaching learning strategy toward learning result of analyzing electrical circuit. The second hypothesis is tested further using dunnet test obtained t count = 11.797 and t table = 1.70. It can be concluded that t count > t table, it is concluded that the result of learning to analyze electrical circuits for students who follow teaching team teaching strategy and have higher motivation higher than students who follow non-team teaching strategies and have high motivation. Results of the third hypothesis obtained t count = 1.81 and t table = 1.70. It can be concluded that t count > t table, it is concluded that the result of learning to analyze electric circuits for students who follow teaching team teaching strategy and have lower motivation lower than students who follow non-team teaching strategy and have low motivation. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh strategi pembelajaran team teaching dan motivasi belajar siswa terhadap hasil belajar menganalisis rangkaian listrik. Penelitian ini dilakukan di SMKN 1 Tambelang pada bulan Februari 2017. Sampel dari penelitian ini adalah siswa yang terdiri dari 2 kelas yaitu kelas eksperimen dari siswa yang diajar dengan team teaching berjumlah 30 siswa dan kelas kontrol dari siswa yang diajar non-team teaching terdiri dari 30 siswa sehingga total berjumlah 60 siswa. Dari 60 siswa tersebut diberikan kuisioner tentang motivasi belajar siswa, hasilnya akan dikelompokkan menjadi 2 bagian yaitu siswa yang memiliki motivasi tinggi dan siswa yang memiliki motivasi rendah Uji hipotesis dengan uji F Anava 2X2 dengan taraf signifikan 0,05. Dari hasil pengujian diperoleh nilai Fhitung antar perlakuan = 49,824 dan F tabel = 4,196. Dapat disimpulkan bahwa Fhitung > F tabel, maka diperoleh kesimpulan bahwa secara keseluruhan terdapat perbedaan nyata antara strategi pembelajaran team teaching dan non – team teaching terhadap hasil belajar menganalisis rangkaian listrik. Hipotesis kedua dilakukan uji lanjut menggunakan uji dunnet diperoleh thitung =11,797 dan t tabel = 1,70. Dapat disimpulkan bahwa thitung > t tabel , maka diperoleh kesimpulan yaitu hasil belajar menganalisis rangkaian listrik bagi siswa yang mengikuti strategi pembelajaran team teaching dan memiliki motivasi tinggi lebih tinggi daripada siswa yang mengikuti strategi pembelajaran non – team teaching dan memiliki motivasi tinggi. Hasil hipotesis ketiga diperoleh thitung =1,81 dan t tabel= 1,70. Dapat disimpulkan bahwa thitung > t tabel , maka diperoleh kesimpulan yaitu hasil belajar menganalisis rangkaian listrik bagi siswa yang mengikuti strategi pembelajaran team teaching dan memiliki motivasi rendah lebih rendah daripada siswa yang mengikuti strategi pembelajaran non – team teaching dan memiliki motivasi rendah.